Globalisasi dan Dampaknya terhadap Lingkungan dan Keamanan Manusia di Asia Pasifik: Kasus China dan Papua Nugini - Ulil Amri (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2011)
This article attempts to show that globalizationto wide extentis closely connected to environmental degradation and human security. Two cases from Asia Pacific countries such as China and Papua New Guinea are selected and elaborated to reveal the connection. Besides, this article shows that half-hearted comitment of the government of both countries to combat environmental degradation continues to threaten human security.Keywords: globalization, environmental degradation, human security, China, Papua New Guinea